PENERAPAN PRINSIP FIREWALL DI HARIAN MANADO POST (On The Application of Firewall Principle in Manado Post Daily) - Lamalo, Arlyn A. (ACTA DIURNA KOMUNIKASI, 2013)
The Manado Post daily does not use the firewall principle linked with media loyalty and integrity. Manado post journalists bid to the peoples the advertisements, especially the advertorials, to get earnings, which can lower the loyalty as journalist. Since journalists has to consider the public interest not the individual, group or business interest. Keywords : Firewall principle, Advertorial, Public Interest